Leveraging observations of Security Force Assistance in Afghanistan for global operations - Payne, Leslie Adrienne (Research report (Rand Corporation), 2013)
The U.S. Army's Asymmetric Warfare Group (AWG) requested that the RAND Corporation conduct a study on how to leverage observations from Security Force Assistance (SFA) efforts in Afghanistan for global operations. Researchers interviewed 67 advisors and SFA practitioners at the tactical and operational levels to collect their firsthand insights into SFA. Interviewees included members of security force assistance teams and Special Forces Operational Detachments-Alpha, senior leadership at the brigade level, and AWG Operational Advisers. The enduring nature of most of these challenges suggests that solutions still remain uncertain. Future SFA missions, such as those envisioned for the Army's Regionally Aligned Forces, can benefit from the experience gained from SFA in Afghanistan as captured in this report. These lessons need to be incorporated both at the institutional level and by individual SFA advisers.